Holocene interplay between a dune field and coastal lakes in the Quiaios– Tocha region, central littoral Portugal - Danielsen, Randi (2012)
Coastal dune fields and dune-body associated lakes were studied through sedimentological, malacological and palynological analyses. Lake deposits and palaeosoil horizons gave new information about phases of aeolian activity and dune building, coastline and sea level, vegetation history and cultural impact. After a period of intense aeolian activity (Late Pleistocene) that limited soil-forming processes, a wet aeolian field, recorded by podzolized sands and interdune wetland deposits, was present in the region. Around 5000 to 4000 yr BP sea level reached the current level and the coastline was situated c. 1 km further inland compared with the present situation. Subsequently lagoon-barrier island systems developed c. 4000 yr BP. Vegetation in the region during this time was a pine/oak forest. Between 4000 and 1600 yr BP the forest was replaced by a semi-natural heathland. Later the heathland was degraded, allowing dune migration and finally formation of a desert-like landscape. This process was probably a consequence of a combination of deteriorating climate during the ‘Little Ice Age’ (LIA) and overgrazing. To counteract sand invasion, reforestation efforts were initiated in the region c. 300 years ago and locally along the coastal margin between 1924 and 1940. Formation of the row of freshwater lakes bordering the dune field at present was contemporaneous with the initial reforestation phase. A close relation between lake formation and accumulation of sand dunes was found. Various types of dunes were identified, truncated dunes, parabolic dunes and transverse/oblique dunes. Dune migration caused an eastward displacement of lakes.